Study of Security Layers Under Attack on Different Layers of Cloud Computing - Fakhreldin, Mohammed Adam Ibrahim; Solanki, Dhanesh; Jasni, Mohamad Zain; Mazlina, Abdul Majid; Mohamad Fadli, Zolkipli (Landesmuseum Kärnten, 2014)
These Days every company is working towards the cloud computing because of its platform and wide-world useful environments and accessible from any place but this platform contain lots of threats with itself of hacking, attack by different sources and virus too but the main problem of big data in cloud is to solve it complexity and correct node of access from correct output.